Quantitation of Fibrin Deposition and Elimination in Organs of Rats Injected with Labelled Fibrinogen by Isolation of the Labelled Fibrin from Water Soluble Tracer - Busch, Christer; Rammer, Lennart (Thrombosis and Haemostasis, 1973)
A method for direct quantitation of fibrin in organs after intravascular coagulation in rats injected with labelled fibrinogen is described. After homogenization and centrifugation of the tissue the fibrin can be measured in the pellet, while the water soluble tracer largely remains in the supernatant.